From Foundation to Acceleration: An Analysis of Indonesia's Two-Decade PPP Journey - Ade Hendraputra (The Journal of Indonesia Sustainable Development Planning, 2026)
Indonesia faces a substantial infrastructure gap, making Public-Private Partnerships (PPPs) critical to address financing challenges. This study discusses Indonesia's PPP framework evolution across two decades (2005-2024), exploring why progress differed markedly between the "foundational decade" (2005-2014) and "acceleration decade" (2015-2024). Using mixed-method explanatory sequential design, we combined PRISMA-compliant Systematic Literature Review of 78 studies with qualitative case analysis of two breakthrough projects—the Central Java Power Plant (PLTU Batang) and the SPAM Umbulan water supply system. Findings challenge the notion that early years represented failure. Rather, post-2015 breakthroughs resulted from targeted land acquisition reforms and institutional maturation of entities like PT PII. Notably, the Viability Gap Fund (VGF) functioned not merely as financial subsidy but as political coordination mechanism among stakeholders. We argue Indonesia's experience exemplifies policy-oriented learning—the foundational decade represented essential investment in "soft infrastructure" enabling later achievements. This evolutionary view offers a roadmap for the institutional development of other emerging economies, particularly regarding the sequencing of regulatory reform and the design of state guarantee mechanisms.